Question
upstudy study bank question image url

3.2. Without using a calculator, simplify: \( \cos 20^{\circ} \cos 320^{\circ}-\sin 160^{\circ} \sin 40^{\circ} \)

Ask by Ford Salazar. in South Africa
Feb 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified value of the expression is \( \frac{1}{2} \).

Solution

To simplify the expression   cos 20° · cos 320° – sin 160° · sin 40°, first notice that cos 320° can be rewritten using the cosine of a complementary angle:   cos 320° = cos (360° – 40°) = cos 40°. Also, recognize that sin 160° is equivalent to sin 20° because   sin 160° = sin (180° – 20°) = sin 20°. Substituting these into the expression gives:   cos 20° · cos 40° – sin 20° · sin 40°. Now, use the cosine addition formula, which states:   cos(A + B) = cos A · cos B – sin A · sin B. Here, take A = 20° and B = 40°. Thus:   cos(20° + 40°) = cos 20° · cos 40° – sin 20° · sin 40°. Since 20° + 40° = 60°, we have:   cos 60° = cos(20° + 40°). And we know:   cos 60° = ½. Therefore, the simplified value of the original expression is ½.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To simplify \( \cos 20^{\circ} \cos 320^{\circ}-\sin 160^{\circ} \sin 40^{\circ} \), we can use the cosine angle subtraction identity. First, note that \( \cos 320^{\circ} = \cos(360^{\circ} - 40^{\circ}) = \cos 40^{\circ} \). Therefore, the expression becomes: \[ \cos 20^{\circ} \cos 40^{\circ} - \sin 160^{\circ} \sin 40^{\circ} \] Next, we recognize that \( \sin 160^{\circ} = \sin(180^{\circ} - 20^{\circ}) = \sin 20^{\circ} \). Thus, we can rewrite the expression as: \[ \cos 20^{\circ} \cos 40^{\circ} - \sin 20^{\circ} \sin 40^{\circ} \] Now, we can apply the cosine subtraction formula: \[ \cos A \cos B - \sin A \sin B = \cos(A + B) \] By setting \( A = 20^{\circ} \) and \( B = 40^{\circ} \), we get: \[ \cos(20^{\circ} + 40^{\circ}) = \cos 60^{\circ} \] Since \( \cos 60^{\circ} = \frac{1}{2} \), the original expression simplifies to: \[ \frac{1}{2} \] Therefore, the final simplified result is: \[ \boxed{\frac{1}{2}} \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy